Portfolio: comparison for Islamic and conventional unit trust performance / Maz Raszia Ellysha Mohd Rasul - Mohd Rasul, Maz Raszia Ellysha (2016)
The Malayan Unit Trust Ltd. formerly was establish which pointed as a starter for the concept of Unit Trust in Malaysia. Unit trust describe as the collective investment schemes that has been manage by the professionally personnel where is their objectives turn similar in order to pool all the investor fund to being invest in the porffolio of securities or other assets (FIMM, 2014).